Iron Fortification and bioavailibility of homemade tempeh with sesame seed - Fauzan Amin; Micha Mahardika; Dianastya Yuniarti (Jurnal Pendidikan Kimia (JPKim), 2020)
Iron deficiency anemia is caused by the low intake of iron from foods. The purpose of this research was to make fortified tempeh using sesame seed with a high potential utility as iron fortificant. The iron bioavailability was carried out in vitro  by simulating human digestion for raw and cooked tempeh. The iron fortificant added were 0, 10, 20, 25, 30 ,40 and 50% of sesame seed to substitute 100 grams of  soybeans. The results of this study showed that the highest Fe content of 0.4539 mg was obtained by replacing 50% soybean with sesame seed. But after cooking, there is a decrease in boiled for 10, 20, 30,40,50% variants and increase in fried for 0, 10, 25, 30% variants.Keywords: Anemia, Tempeh, Fortification, Sesame seed